2019
DOI: 10.1002/adtp.201900088
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green–Coated Gold Nanoclusters for Photoacoustic Imaging and Photothermal Therapy

Abstract: Traditional oncology treatment modalities are often associated with a poor therapeutic index. This has driven the development of new targeted treatment modalities, including several based on the conversion of optical light into heat energy (photothermal therapy, PTT) and sound waves (photoacoustic imaging, PA) that can be applied locally. These approaches are especially effective when combined with photoactive nanoparticles that preferentially accumulate in tissues of interest and thereby further increase spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…A micronanoswarm consisting of small AuNPs was also developed for PTT of breast tumors under NIR laser irradiation (Figure 4a2). 83 The regression of tumor volume can be achieved, indicating the effectiveness of the tumor PTT using the swarm.…”
Section: Design Of Micronanoswarmsmentioning
confidence: 90%
See 1 more Smart Citation
“…A micronanoswarm consisting of small AuNPs was also developed for PTT of breast tumors under NIR laser irradiation (Figure 4a2). 83 The regression of tumor volume can be achieved, indicating the effectiveness of the tumor PTT using the swarm.…”
Section: Design Of Micronanoswarmsmentioning
confidence: 90%
“…Through comparing changes of tumor sections in mice (Figure a1), it can be demonstrated that this swarm was effective for cancer treatment. A micronanoswarm consisting of small AuNPs was also developed for PTT of breast tumors under NIR laser irradiation (Figure a2) . The regression of tumor volume can be achieved, indicating the effectiveness of the tumor PTT using the swarm.…”
Section: Biomedical Applications Of Micronanoswarmsmentioning
confidence: 99%
“…Several classes of molecules, such as tetrapyrrolic macrocycles and analogues, including porphyrins [64][65][66][67][68][69][70][71], phthalocyanines [72,73], chlorins [22,23,[74][75][76][77][78][79][80][81][82][83][84][85][86], the prodrug 5-aminolevulinic acid (5-ALA) [87][88][89] and other dyes, such as adequately conjugated indocyanine green [90][91][92][93][94], have been explored as PS in TNBC targeted therapy. Chlorins and their analogues are very interesting molecules; besides their natural source and/or semi-synthetic preparation, these molecules exhibit good absorption in the therapeutic window (600-800 nm), which is an important feature for a good candidate for clinical PDT, due to the better light penetration in tissues (≈1-2 cm), which overcomes the light penetration limitation when other photosensitizers are used, such as porphyrins [48,49,95].…”
Section: Targeted Therapy In Triple-negative Breast Cancermentioning
confidence: 99%
“…Both in vitro and in vivo evidence indicated that such gold nanoclusters could serve as potent and specific imaging reagents and were highly effective to produce heat, leading to 40% complete remission of the primary tumor and 20% complete disease remission. [ 85 ] Zhao et al constructed multifunctional triangular gold nanoplates for computed tomography (CT)/PAI‐guided PTT of nonsmall‐cell lung cancer. The in vivo CT/PA dual‐imaging modality helped visualize the distribution of nanostructures before the treatment and then depict the boundary of tumors for PTT in a real‐time fashion.…”
Section: Multifunctional Gold Nanomaterials For Light‐mediated Theragnosticsmentioning
confidence: 99%